2007
DOI: 10.1093/occmed/kqm078
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to ionizing and non-ionizing radiation and risk of glioma

Abstract: We did not find evidence of an association between glioma and occupational exposure to ELF, RF and ionizing radiation. UV radiation was associated with increased glioma risk for men but this result could have been confounded by other predominantly male occupational and lifestyle exposures associated with high UV. Further investigation of UV radiation and glioma risk is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 26 publications
0
18
0
4
Order By: Relevance
“…Although the etiology of the higher IR observed in this area remains obscure, it could be partially related to undetermined environmental factors such as higher exposure to sun and ultraviolet radiation [30] . Further studies are needed to investigate the influence of specific environmental factors and the genetic alterations in this area as predisposing to cerebral gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of the higher IR observed in this area remains obscure, it could be partially related to undetermined environmental factors such as higher exposure to sun and ultraviolet radiation [30] . Further studies are needed to investigate the influence of specific environmental factors and the genetic alterations in this area as predisposing to cerebral gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although a possible association between low level medical IR exposure and the risk of brain tumors has been suggested (45, 46), occupational exposure to low IR levels and the risk of brain tumors remains, however, not very consistent (45, 47, 48). In the current study, ten study subjects reported medical exposure to IR (for treatment of conditions such as acne, birth mark, and hyperthyroidism) while the remaining 46 were occupationally exposed (occupations such as physicians, radiologists, nurses, pilots and engineers).…”
Section: Discussionmentioning
confidence: 99%
“…38 Gender differences were also observed in an Australian occupational case-control study that found an inverse association between occupational UV exposure and risk of glioma in females (OR= 0.54; 95% CI= 0.27-1.07) while there was a positive association among males (OR= 1.60; 95% CI= 0.95-2.69). 39 Alternatively, gender differences may also be due to misclassification of occupational exposure due to behavioral differences, such as a higher tendency for females to use sunscreen on a regular basis and the ability of males to work outdoors while shirtless. 40 Around the world (with a few exceptions) males generally tend to go outside more frequently, spend more time outdoors and therefore acquire higher UV doses than females.…”
Section: Discussionmentioning
confidence: 99%